PENGARUH PERSEPSI HARGA TERHADAP MINAT BELI SMARTPHONE OPPO - Melisa Zuriani Hasibuan; Horia Siregar (JURNAL MUTIARA MANAJEMEN, 2021)
This study aims to analyze the effect of price perception on Oppo smartphone buying interest in the community of Sukamulia Village Dusun II, Pagar Merbau District. This research uses a quantitative descriptive approach. With a population of 1,174 respondents with a tolerance limit of 10% which is calculated by the Slovin formula, a total sample of 92 respondents was obtained with a sampling technique using random sampling techniques. Data collection was carried out by giving a list of statements to respondents, namely the people of Sukamulia Village Dusun II, Pagar Merbau District. This study uses the technique of simple Linear Regression Analysis, t test, and the coefficient of determination. The results of multiple linear regression analysis obtained Y = 3.292 + 0.389X. Partial test results (t test) indicate that price perception variable it has a significant effect on buying interest in oppo smartphones. This can be seen from the value of t arithmetic (3,080)> t table (1,662) with a significant 0.003 < 0.05. With an R square value of 0.521. This means that the effect of variable X on variable Y is 52.1%, while the remaining 47.9% is influenced by other variables not included in this study.